Widespread Existence of Quorum Sensing Inhibitors in Marine Bacteria: Potential Drugs to Combat Pathogens with Novel Strategies - Zhao, Jing (Mar Drugs, 2019)
Quorum sensing (QS) is a phenomenon of intercellular communication discovered mainly in bacteria. A QS system consisting of QS signal molecules and regulatory protein components could control physiological behaviors and virulence gene expression of bacterial pathogens. Therefore, QS inhibition could be a novel strategy to combat pathogens and related diseases. QS inhibitors (QSIs), mainly categorized into small chemical molecules and quorum quenching enzymes, could be extracted from diverse sources in marine environment and terrestrial environment. With the focus on the exploitation of marine resources in recent years, more and more QSIs from the marine environment have been investigated. In this article, we present a comprehensive review of QSIs from marine bacteria. Firstly, screening work of marine bacteria with potential QSIs was concluded and these marine bacteria were classified. Afterwards, two categories of marine bacteria-derived QSIs were summarized from the aspects of sources, structures, QS inhibition mechanisms, environmental tolerance, effects/applications, etc. Next, structural modification of natural small molecule QSIs for future drug development was discussed. Finally, potential applications of QSIs from marine bacteria in human healthcare, aquaculture, crop cultivation, etc. were elucidated, indicating promising and extensive application perspectives of QS disruption as a novel antimicrobial strategy.